Coronary Intervention: History and Current Status - Glazier, Catherine R.; Glazier, James J. (International Journal of Angiology, 2025)
On September 16, 1977, Dr Andreas Roland Grüntzig performed the world's first successful percutaneous transluminal coronary angioplasty at the University Hospital Zurich, Switzerland. This spectacular event ushered in the era of interventional cardiology. The technique has had a major influence on the practice of cardiology, right up to the current day. While Grüntzig remains the undisputed father of interventional cardiology, the observations and techniques developed by preceding pioneers in the fields of angiology, radiology, cardiology, and vascular and cardiac surgery paved the way for this procedure. Coronary stents were first developed by Ulrich Sigwart and his team in Lausanne, Switzerland. The aim of the stents was to reduce the considerable rates of restenosis and abrupt closure associated with balloon angioplasty. Current second-generation drug-eluting stents have very low abrupt closure and restenosis rates. Drug-eluting stents have performed favorably when compared with coronary artery bypass surgery in the treatment of patients with complex coronary artery disease. It is estimated that, in approximately one-third of such patients, treatment with these stents is an excellent alternative to coronary artery bypass surgery. Currently, coronary angioplasty with drug-eluting stents remains the preferred treatment of acute myocardial infarction, provided this can be done in timely fashion. With regard to patients with acute coronary syndrome, the benefit for angioplasty is greatest for those patients at moderate to high risk for cardiac complications. It is now accepted that most patients with stable ischemic heart disease are best managed with medical treatment rather than angioplasty.
Keywords: coronary artery disease; percutaneous transluminal coronary angioplasty; coronary stents; drug-coated balloons; intravascular ultrasound; intravascular lithotripsy; Dotter technique